ANALISIS KOMPONEN PERKEMBANGAN WILAYAH PROPINSI LAMPUNG - Nandang Najmulmunir (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2003)
The development of the economic region was dcpcnt on several factors such as natural resources endowment, appropriate policies, infrastructure, economic interaction among kabupaten region and it’s location. Such factor will classified into three components of regional economic development. There arc province development factor, mix development factor and competitive development factor. The performance of combination of the three factors will execute the sector or the administrative region classified as the fast growing or the late growing.